Investigating the Role of Social Capital in Good Urban Governance (Case Study: Semnan) - Ali Akbar Taghipour; Abolfazl Mashayekhi; Ghasem Jafari (برنامه‌ریزی توسعه شهری و منطقه‌ای, 2018)
Urbanization is one of the major challenges facing societies. Governments are largely unable to carry out those tasks, and continuation of the current trend can increase the problems of citizens with urban management. Today the good urban governance is spoken as an appropriate solution to stop the current process. Social capital is one of the effective factors in achieving good urban governance. In this regard, considering the challenges in Semnan, measuring citizens' satisfaction with the performance of urban management and also their role in creating good urban governance is important. In order to study the role of social capital in good urban governance in Semnan, first the definitions of good urban governance and social capital were examined and then the effective indicators of social capital in good urban governance were extracted. Then, citizens' opinions were collected through questionnaire. The results of this research show that the components of social capital and good urban governance in Semnan are not in a good condition and lack of accountability, transparency, collective agreement and legality in Semnan urban governance has caused a loss of trust in urban management and reduced willingness to participate in urban projects. The result is a lack of involvement of citizens in decision-making. Also, the lack of infrastructure such as local council and an appropriate mechanism for public participation in the approval process for projects have been effective.